Thermogravimetric Study of Polyisothiocyanato-Styrenes - AHMED, MEGHEZZI; NIKANOR, BARBA; YOUCEF, LAKHDAR; BELKHIR, DADAMOUSSA; MOKHTAR, SAIDI; LYNDA, DJOUDI (Asian Journal of Chemistry, 2010)
Polyisothiocyanato-styrene (PITCS) was prepared by radical polymerization corresponding monomers. The polymers were characterized by physical and spectral studies. The polymer showed excellent stability. Their inherent viscosities were in the range of 0.26-0.32 dL/g. Thermal study of the polymers, poly-2, poly-3, poly-4-isothio-cyanatostyrene, poly-2,4-diisothiocyanato-styrene and 4-isothio-cyanatostyrene oligomer show, the increase of temperature till 230°C. After that they transform into three dimensional structure without the weight loss. However, because of this structure the weight decreases slowly and their destruction temperature exceeds that of the polystyrene by a temperature varying from 220-230°C. The weight loss speed is tightly linked to the 4-isothiocyanato-styrene oligomer.